Gardenia - Selig, SarahBelle (School of Languages and Literatures, 2023)
Ellen is 29 and disillusioned with her advertising job in New York when she receives an email from a woman named Isa, for whom Ellen's mother Lacey abandoned her family fifteen years prior. In the email, Isa attempts to explain her affair with Lacey, who was almost two decades older than her at the time, and what happened in the years following the affair's discovery that led to Lacey's eventual mental and physical collapse. As Ellen travels back to coastal North Carolina to discover what happened to Lacey after she disappeared and face the one woman she has long blamed for it, she must confront the responsibility she, her father and brothers share in pushing her mother towards Isa, and reconcile with the abuse her family has inflicted on Isa in the years since. Gardenia is told in three intertwined novellas. In "Dig", Lacey begins a string of reckless acts in an attempt to assert herself amidst her lonely motherhood, including an affair with the young, black Isa. In "Sow", Isa recounts the story of her relationship with Lacey to her now husband, detailing her attempts to save the woman she loved from addiction while coping with her own increasing isolation from friends and family. Finally, in "Reap", Ellen contemplates her mother's decisions amidst the rapidly changing landscape of women's rights post-#MeToo, while battling her own demons and justifying to her younger brother her decision to find Isa. In each novella, the main character makes a different choice on what to do with her trauma, when faced with the opportunity to leave it behind. A reflection on the unbridgeable distance between the sexes, culminating in a meeting between the two women most haunted by Lacey's absence, Gardenia explores victimhood, women's sexuality, how we leave each other and—as each woman discovers—how we never really do.